2010
DOI: 10.1096/fj.10-170597
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signaling 1 (SOCS1) limits NFκB signaling by decreasing p65 stability within the cell nucleus

Abstract: Suppressor of cytokine signaling (SOCS) proteins are inhibitors of cytoplasmic Janus kinases (Jak) and signal transducer and activator of transcription (STAT) signaling pathways. Previously the authors surprisingly observed that SOCS1 translocated into the nucleus, which was because of the presence of a nuclear localization sequence. This report now hypothesizes that SOCS1 mediates specific functions within the nuclear compartment because it is instantly transported into the nucleus, as shown by photoactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 46 publications
6
133
0
1
Order By: Relevance
“…Whereas these preceding studies suggest the mechanism of SOCS1 action in suppressing nuclear NF-kB activity and the target gene expression at the molecular level, our work presents a complete system where such inhibitory action of SOCS on the NF-kB activation via expression of specific gene products translates into the regulation of cell survival response against apoptotic stimuli in a defined cell type. Strebovsky et al (32) reported a lack of SOCS3 regulation of p65 in their experimental system. We have, however, shown in human leukemic Jurkat T cells that SOCS3 also acted as a potent proapoptotic factor during the Fas-induced cell death with suppressive effects on NF-kB activation and Bfl-1 expression.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Whereas these preceding studies suggest the mechanism of SOCS1 action in suppressing nuclear NF-kB activity and the target gene expression at the molecular level, our work presents a complete system where such inhibitory action of SOCS on the NF-kB activation via expression of specific gene products translates into the regulation of cell survival response against apoptotic stimuli in a defined cell type. Strebovsky et al (32) reported a lack of SOCS3 regulation of p65 in their experimental system. We have, however, shown in human leukemic Jurkat T cells that SOCS3 also acted as a potent proapoptotic factor during the Fas-induced cell death with suppressive effects on NF-kB activation and Bfl-1 expression.…”
Section: Discussionmentioning
confidence: 93%
“…Our data further show that SOCS1 coimmunoprecipitates p65 as well as p50, suggesting the molecular interaction of SOCS1 with the NF-kB complex of p65/p50. Of note, while this manuscript was in preparation, SOCS1 action to limit the duration NF-kB signaling through SOCS box-mediated p65 degradation in the nucleus was reported using kB-dependent reporter gene assays in SOCS1-transfected HEK 293 cells (32). Whereas these preceding studies suggest the mechanism of SOCS1 action in suppressing nuclear NF-kB activity and the target gene expression at the molecular level, our work presents a complete system where such inhibitory action of SOCS on the NF-kB activation via expression of specific gene products translates into the regulation of cell survival response against apoptotic stimuli in a defined cell type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it was shown that SOCS1 contributes to ubiquitination and subsequent degradation of NF-kB (31,32), thereby modulating a subset of NF-kB-induced genes, we wanted to analyze whether activation of NF-kB transcription factors after costimulation with CpG-DNA and dZ was altered. We first tested whether the costimulation causes an increase in SOCS1 expression.…”
Section: Dna In Ifn-gmentioning
confidence: 99%
“…Известно, что белок SOCS1 взаимодействует с Toll-подобным рецептором (TLR), белками NF-κB и p53, за счет чего может играть роль в процессе подавления канцерогенеза [24][25][26][27]. Кроме того, SOCS1 может способствовать фосфорилированию р53 и его активации, что приводит к реализации зависимых от р53 процессов в активированной онкогенами клетке [28,29].…”
unclassified